The Fairytale and Plot Structure - Murphy, Terence Patrick. author. aut Link
XIX, 204 p.
Keywords: This book offers a detailed exploration of the plot genotype, the functional structure behind the plots of classical fairy tales. By understanding how plot genotypes are used, the reader or creative writer will obtain a much better understanding of many other types of fiction, including short stories, dramatic texts and Hollywood screenplays.